Some Transition Metal Complexes of N-(Glycyl)-α-Picolylamine and Its Schiff Base - Yüksel, Mithat; Ekk[acaron]roĝlu, Özer (Informa UK Limited, 1982)
Abstract The complex formation of N-(glycyl-α-picolylamine), (GPAH) and its Schiff base from salicylaldehyde with Cu(II), Ni(II), Zn(II), Cd(II), Hg(II), Co(II), Co(III) metal ions under several conditions was investigated. Structures for the isolated Schiff base and the new complexes were proposed based on n.m.r., i.r., u.v.-visible spectra and elemental analyses.